Gird Congestion Management Based on the Renewable Energy Zones and Clustering of Grid Congestion Conditions - Yujiro Tanno; Akihisa Kaneko; Yasuhiro Hayashi; Yuki Itoda; Wataru Wayama; Kevin Tomsovic (IEEE Access)
This study proposes a novel output curtailment method of renewable energy sources (RESs) to mitigate grid congestion while balancing curtailment minimization and fairness among power producers, considering the operational efficiency of system operators. This method is based on creating zones using sensitivity analysis and clustering grid congestion conditions. Recently, the large introduction of RESs has raised concerns of grid congestion in power systems. To mitigate congestion, the system operator curtails the output of RESs; however, the curtailment should be minimized while ensuring equal generation opportunities among power producers. The proposed method divides RESs into multiple zones according to the congestion mitigation effect of their output curtailment and uniformly curtails them in each zone. Moreover, the method divides congestion conditions throughout the year by clustering and creates zones of RESs for each congestion pattern. This approach aims to apply the optimal zone division of RESs according to the congestion condition, while removing the burden on the operator to recreate the zone division for each time step. A simulation was conducted to evaluate the effectiveness of the proposed method using a bulk power system model in the northern area of Tohoku region of Japan. Based on the simulation results, our proposed method outperforms existing approaches in terms of minimizing RES curtailment and promoting fairness across power producers, while considering the frequency of zonal creation.